tính hợp lí : 4/5-2/9.(-3)^2+9/2:3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{5}{8}+\frac{2}{9}-\frac{2}{5}+\frac{3}{8}+\frac{4}{9}+\frac{1}{3}-\frac{3}{5}\)
\(=\frac{5}{8}+\frac{2}{9}-\frac{2}{5}+\frac{3}{8}+\frac{4}{9}+\frac{3}{9}-\frac{3}{5}\)
\(=\left(\frac{5}{8}+\frac{3}{8}\right)+\left(\frac{2}{9}+\frac{4}{9}+\frac{3}{9}\right)-\left(\frac{2}{5}+\frac{3}{5}\right)\)
\(=\frac{8}{8}+\frac{9}{9}-\frac{5}{5}\)
\(=1+1-1\)
\(=2-1\)
\(=1\)
a)\(-\dfrac{2}{5}.\dfrac{4}{7}+\dfrac{-3}{5}.\dfrac{2}{7}+\dfrac{-3}{5}\)
=\(-\dfrac{2}{5}.\dfrac{4}{7}+\dfrac{3}{7}.\dfrac{-2}{5}+\dfrac{-3}{5}\)
=\(-\dfrac{2}{5}.\left(\dfrac{4}{7}+\dfrac{3}{7}\right)+\dfrac{-3}{5}\)
=\(\dfrac{-2}{5}.1+\dfrac{-3}{5}\)
=\(-\dfrac{2}{5}+\dfrac{-3}{5}\)
=\(-\dfrac{5}{5}\) = -1
\(\dfrac{5}{9}.\dfrac{14}{17}+\dfrac{1}{17}.\dfrac{5}{9}+\dfrac{2}{9}+\dfrac{5}{12}\)
=\(\dfrac{5}{9}.\left(\dfrac{14}{17}+\dfrac{1}{17}\right)+\dfrac{2}{9}+\dfrac{5}{12}\)
=\(\dfrac{5}{9}.\dfrac{15}{17}+\dfrac{2}{9}+\dfrac{5}{12}\)
=\(\dfrac{25}{51}+\dfrac{2}{9}+\dfrac{5}{12}\)
=\(\dfrac{691}{612}\)
\(S=\dfrac{3}{4}-\dfrac{1}{4}-\left(\dfrac{7}{3}-\dfrac{9}{2}\right)-\dfrac{5}{6}\)
\(=\left(\dfrac{3}{4}-\dfrac{1}{4}+\dfrac{18}{4}\right)-\left(\dfrac{14}{6}+\dfrac{5}{6}\right)\)
\(=\dfrac{20}{4}-\dfrac{19}{6}=\dfrac{11}{6}\)
`a)3/5+(-4/9)`
`=3/5-4/9`
`=27/45-20/45`
`=7/45`
`b)3/5+2/5 . 15/8`
`=3/5 + 30/40`
`=3/5+3/4`
`=12/20+15/20`
`=27/20`
`c)7/2 . 8/13 + 8/13 . (-5/2)`
`=8/13 . (7/2 +(-5)/2)`
`=8/13 . 1`
`=8/13`
`d)-5/17 . (-9/23)+9/23 . (-22/17) + 11 9/23`
`=-5/17 . (-9/23) + 9/23 . (-1) . 22/17 + 11 + 9/23`
`=-5/17 . (-9/23) + (-9/23) . 22/17+11+9/23`
`= -9/23 ( -5/17 + 22/17)+11+9/23`
`= - 9/23 . 1+11+9/23`
`=-9/23+11+9/23`
`=(-9/23+9/23)+11`
`=0+11`
`=11`
a: =27/45-20/45=7/45
b: =3/5+30/40
=3/5+3/4
=12/20+15/20
=27/20
c: =8/13(7/2-5/2+1)=8/13*2=16/13
d: =9/23*5/17-9/23*22/17+11+9/23
=-9/23+11+9/23
=11
a: =-21/36-3/36=-24/36=-2/3
b: =43/12*1/2+5/24=43/24+5/24=2
c: =8/9+1/9=1
e: =1-1/4+1/4-1/7+...+1/97-1/100
=1-1/100=99/100
\(\dfrac{4}{5}-\dfrac{2}{9}\times\left(-3\right)^2+\dfrac{9}{2}\div3\)
\(=\dfrac{4}{5}-\dfrac{2}{9}\times9+\dfrac{3}{2}\)
\(=\dfrac{4}{5}-2+\dfrac{3}{2}\)
\(=-\dfrac{6}{5}+\dfrac{3}{2}\)
\(=\dfrac{3}{10}\)
\(\dfrac{4}{5}-\dfrac{2}{9}.\left(-3\right)^2+\dfrac{9}{2}:3\)
\(=\dfrac{4}{5}-\dfrac{2}{9}.9+\dfrac{9}{2}.\dfrac{1}{3}\)
\(=\dfrac{4}{5}-2+\dfrac{3}{2}\)
\(=\dfrac{8}{10}-\dfrac{20}{10}+\dfrac{15}{10}\)
\(=\dfrac{3}{10}\)